The Nutritional And Antinutritional Composition Of Strobilanthes Crispus (L.)Bremek And Its Anticancer Effect During Hepatocarcinogenesis - Manickam, Elizabeth (1999)
The nutritional and antinutritional composition of Strobilanthes crispus (L. ) Bremek or Saricocalyx crispus (L.) Bremek (Acanthacea) , and its anticancer effect during hepatocarcinogenesis were studied to investigate the possible cancer suppressive effect of the component existed in the leaves. The nutritional composition studied were of the proximate composition and antioxidant activity of ferric thiocyanate and thiobarbituric acid methods. The antinutritional factors studied were catechin, tannin, caffeine and alkaloid. All data were compared to Yerbamate, green tea, black tea and Indian tea. The leaves contained high amount of water soluble vitamins and total ash leading to high amount of minerals such as potassium, calcium, sodium, iron and phosphorus. The leaves contained low level of antinutritional factors contributing to better absorption of iron and water soluble vitamins. Its catechins showed highest antioxidant activity when compared to Yerbamate and Vitamin E.